2007
DOI: 10.1375/twin.10.2.385
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Analysis of Placentas From Twin Pregnancies Derived From Assisted Reproductive Technology

Abstract: There are conflicting studies associating twin pregnancies derived from assisted reproductive technology (ART) with preterm birth, low birthweight, and other negative outcomes. This work investigates whether ART is linked with any placental pathology, given that placentation significantly influences fetal development. A 5-year, retrospective cohort study was conducted on placentas from twin pregnancies. The placental information from 417 patients was divided into two groups: placentas derived from ART and plac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 52 publications
0
2
0
1
Order By: Relevance
“…In spontaneously-conceived twin pregnancies, the prevalence of dizygotic twinning varies with race and ethnicity, from a low of 1.3/1,000 live births in Asia to 50/1,000 live births in Africa, as well as increasing with the maternal factors of older age, taller height, higher parity, and family history of twinning (58, 59). Prior to the advent of assisted reproductive technologies, the rate of monozygotic twinning was relatively constant worldwide at about 4/1,000 live births, regardless of maternal or familial factors (60); it has been estimated that the incidence has more than doubled with assisted conception (8–9/1,000 live births) (61, 62). In ART treatment, the main risk factor for dizygotic twins and higher-order multiple pregnancies is the transfer of more than one embryo (63, 64), as well as taller maternal stature (>68 inches) and higher number of oocytes retrieved (>8) (65).…”
Section: Discussionmentioning
confidence: 99%
“…In spontaneously-conceived twin pregnancies, the prevalence of dizygotic twinning varies with race and ethnicity, from a low of 1.3/1,000 live births in Asia to 50/1,000 live births in Africa, as well as increasing with the maternal factors of older age, taller height, higher parity, and family history of twinning (58, 59). Prior to the advent of assisted reproductive technologies, the rate of monozygotic twinning was relatively constant worldwide at about 4/1,000 live births, regardless of maternal or familial factors (60); it has been estimated that the incidence has more than doubled with assisted conception (8–9/1,000 live births) (61, 62). In ART treatment, the main risk factor for dizygotic twins and higher-order multiple pregnancies is the transfer of more than one embryo (63, 64), as well as taller maternal stature (>68 inches) and higher number of oocytes retrieved (>8) (65).…”
Section: Discussionmentioning
confidence: 99%
“…Although the results showed that twins with dizygosity by restriction to 'unlike sex' had beneficial outcomes among the ART group, the authors indicated that it was doubtful to generalize this subset of dizygotic twins to all dizygotic twin deliveries. Most studies regarding chorionicity analyzed gender difference to define dizygosity because it was largely contributed to the dichorionic placentation, however, a possible explanation about dizygous monochorionic twinning has been propounded by several reports and dizygosity could not be determined by gender (Chan et al, 2007;Souter et al, 2003). In investigation to evaluate the gender mix of twin pregnancies, moreover, the gender combination might influence the length of gestation and birthweight independent of chorionicity (James, 2002;Luke et al, 2005).…”
Section: Twin Research and Human Genetics February 2011mentioning
confidence: 99%
“…A incidência da gestação monozigótica é de aproximadamente 1 em 250 gestações e relativamente constante em todas as populações, independente da raça, idade ou paridade materna [34,54] . No entanto, estudos têm demonstrado aumento das gestações monozigóticas relacionado com as técnicas de reprodução assistida, principalmente devido à duração do intervalo entre a formação do zigoto e a implantação dele na cavidade uterina [55,56] .…”
Section: Técnicas De Reprodução Assistidaunclassified